Accesibility of facilities for disabled person at musolla in shopping complex / Nurul Nawwar Hanim Ahmad Nasir - Ahmad Nasir, Nurul Nawwar Hanim (Faculty of Architecture, Planning and Surveying, 2015)
The purpose of this research is to study and improve the design and facilities in buildings to cater for the disabled people. This study highlights the existing design and facilities provided in musolla at shopping complex. The definition and issues of disability, design principles, regulations and guidelines are emphasize in chapter 2. Plus, there are three types of research methods used are indicated in chapter 3. Moreover, three case studies of musolla at shopping complex are executed to observe whether the related facilities are complied with building regulations and requirements by using checklists provided. Besides, questionnaire are deliberated and executes in order to find out the problems exist on design and to discover the dissatisfaction of the disables party while they are using the facilities in the buildings. Factors that caused failure to provide the disabled facilities are public discrimination, impartially of human rights against the disabled, comportment of local authorities, developer and town planner. It led to the problems such as inappropriate design of facilities, impracticable facilities provided, facilities are inadequately provided, and lack of understanding on disabled needs and no strict enforcement of building by -law still exist in building. Some recommendation collected through studies to improve the facilities are to seek and obtain recommendation from the disabled, motivating them to participate and give opinions on facilities at discussion stage. Local authorities should impose penalty for non-compliance, negotiate with and give incentive to developers, learning from the west to provide sufficient education for public. Finally, the conclusion and recommendations will be done based on the analysis for the case studies, checklist and questionnaire.